SQL-based analytic algorithm for clustering - HILDRETH JAMES DEAN (2004)
A method, apparatus, and article of manufacture for performing data mining applications in a relational database management system. An analytic algorithm for clustering is performed by the computer. The analytic algorithm for clustering includes SQL statements performed by the relational database management system for reducing data retrieved from the relational database in bulk, and programmatic iteration for operating on the reduced data to find clusters therein. The analytic algorithm for clustering creates at least one analytic model within the analytic logical data model from data residing in the relational database.